DETERMINAN COMPANY VALUE PADA SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI - Natasya Widya Utomo Putri, (2021)
The purposes of this research are to assess the effect of Profitability, Business Risk, and Intellectual Capital on Company Value. The population is all companies which engaged in the field of mining sector listed in Indonesia Stock Exchange (IDX). By using Slovin sampling, obtained 44 mining companies with research period of four years to obtain 176 sampel units. Data analysis has been carried out by using panel data regression analysis with Eviews 11 and significant level 5%. The result of this research show that Profitability as measured by Return on Equity (ROE) does not give any influence to the Company Value, Business Risk as measured by Business Risk (BRISK) give positive influence to the Company Value, and Intellectual Capital as measured by Value Added Intellectual Capital (VAIC™) does not give any influence to the Company Value.